Why you do what you do: The power in knowing and naming pedagogies - Gin, Deborah H. C. (Teaching theology and religion, 2019)
This article is for those educators who want to become more intentional in their craft of teaching. The authors introduce eight different pedagogies through their historical lineage, intending for readers to gain an appreciation for, and understanding of, the broader trajectory of educational philosophies, and illustrate how common teaching techniques can be shaped by the pedagogies. By familiarizing themselves with a specific educational philosophy or philosophies, educators begin to identify and name the ways they teach, how students best learn, what counts as knowledge, and the desired outcomes. In doing so, educators increase their opportunities to provide more meaningful and impactful education. This article also includes quick-reference guides to the pedagogies for readers to return to frequently.